Gastronomy in modern times - Álvarez Alfeirán, Luis Javier (2016)
To make a difference between globalisation and multiculturality give us the opportunity to move from a universal classification to a social and individual sense where the person is or should be the centre of the discussion.In this article we speak about the identity that the person must have in a world that goes beyond globalisation looking within multicultural experiences his/her sense of uniqueness. In the world of gastronomy, as in many others, there has been a social and cultural change where cooks have left behind the doors of their kitchens in order to become rock stars being very much present on the mass media, although the fundamental part is their person and not the personification that has been intended to be created.